Nowe prawa i obowiązki ratowników medycznych w świetle nowelizacji ustawy o PRM = New rights and duties of paramedics according to the updated Law on National Medical Emergency Services - Mikos, Marcin; Juszczyk, Grzegorz; Czerw, Aleksandra (Journal of Education, Health and Sport, 2016)
Mikos Marcin, Juszczyk Grzegorz, Czerw Aleksandra. Nowe prawa i obowiązki ratowników medycznych w świetle nowelizacji ustawy o PRM = New rights and duties of paramedics according to the updated Law on National Medical Emergency Services. Journal of Education, Health and Sport. 2016;6(2):311-315. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.46832 http://ojs.ukw.edu.pl/index.php/johs/article/view/3409 https://pbn.nauka.gov.pl/works/717768 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.01.2016. Revised 12.02.2016. Accepted: 27.02.2016. Nowe prawa i obowiązki ratowników medycznych w świetle nowelizacji ustawy o PRM New rights and duties of paramedics according to the updated Law on National Medical Emergency Services Marcin Mikos (1), Grzegorz Juszczyk (2), Aleksandra Czerw(2) (1) Polskie Towarzystwo Prawa Medycznego (2) Warszawski Uniwersytet Medyczny, Zakład Zdrowia Publicznego Słowa kluczowe: ratownik medyczny, Państwowe Ratownictwo Medyczne. Key words: medical profession of paramedics, The Law on National Medical Emergency Services. Streszczenie Zmiany w prawie dotyczące wykonywania zawodu ratownika medycznego są źródłem nowych praw i obowiązków w zakresie wykonywania tego zawodu w Polsce. Nowe przepisy wprowadzają także ustawowe gwarancje przestrzegania praw pacjenta przez ratowników medycznych. W pracy opisane zostały najważniejsze zmiany wynikające z nowelizacji z dnia 25 września 2015 roku ustawy o Państwowym Ratownictwie Medycznym mające bezpośredni wpływ na uwarunkowania zawodowe paramedyków. Abstract Changes in the law regulating medical profession of paramedics are fundamental sources of new rights and duties of this occupation in Poland. New regulations introduce legal boundaries for obeying the patients’ rights by paramedics. The paper describes the key changes based on the update of the Law on National Medical Emergency Services form 25th of September 2015, which directly influence occupational duties of paramedics in Poland.